If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 0 = 6y Reorder the terms: 0 + -2y = 6y Remove the zero: -2y = 6y Solving -2y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -2y + -6y = 6y + -6y Combine like terms: -2y + -6y = -8y -8y = 6y + -6y Combine like terms: 6y + -6y = 0 -8y = 0 Divide each side by '-8'. y = 0 Simplifying y = 0
| (4x-10)(-2)= | | 140=3x+8x+8 | | 5a+7=3a+39 | | 6w-10+-18w= | | 2(30)+8= | | 4+8=36 | | 1-(1/2)(-x+5)=2+3(1-x) | | 15-4x=32 | | 7x-5(2x+2)=-19 | | -14p=156 | | 5+5y-5y=5 | | 17+x=3+17 | | -2(x-8)=6(x+4)-8 | | 5x+8-7x-12= | | y=2x^2+36x+168 | | 5y+6x-3y-5x+4x= | | 5y+6x-3y-5y+4x= | | 15m-9=21 | | -2(x-8)=(6x+4)-8 | | 3.45x+2.5y=52 | | 2r-5=1r | | -2x(x-8)=(6x+4)-8 | | -6r-10s+8r+4s-6= | | x^2+2x=89 | | 3x^4+9x^3-25x^2+15x-50=0 | | 2(5+-.5y)+y=10 | | 9y-2+9y=6 | | 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 | | 7t-4.6=10.1 | | 3(xy+w*w)+2xy-2w*2w= |